THE ROLE OF MARYAM'S SPIRITUAL INTELLIGENCE AS A SINGLE PARENT MOTHER (STUDY OF THEMATIC INTERPRETATION) (International Conference on Social and Islamic Studies, 2022)
The focus of this article is to reveal the role of Maryam Ibu Isa's spiritual intelligence as a single parent so that she is able to educate Prophet Isa as. The research methodology used is library research, the type of research is descriptive qualitative and uses the approach of psychology and thematic interpretation. The results of the research show that in the Qur'an, especially QS Ali Imran and QS Maryam, Allah SWT describes Maryam's life from before birth until gave birth to Jesus The long journey throughout Maryam's life as an orphan, until Allah SWT gave her the mandate of Prophet Isa as a child resulted in quite big problems and tests that were very difficult to face. However, thanks to the role of spiritual intelligence that Maryam possessed, all of that was surpassed and she succeeded in educating her son Prophet Isa as a single parent. Prophet Isa grew into a great person, full of compassion and love thanks to his mother's education. Allah SWT raised Prophet Isa as a Prophet and Messenger who earned the nickname of a famous person in the world and the hereafter and was one of the closest people to Allah SWT.